Hyaenidae (Carnivora) from the Late Miocene hominid locality of Hammerschmiede (Bavaria, Germany). (2nd November 2022) - Kargopoulos, Nikolaos; Kampouridis, Panagiotis; Lechner, Thomas; Böhme, Madelaine
ABSTRACT: The present paper deals with new hyaenid material from the locality of Hammerschmiede (Bavaria, Germany). The described specimens are attributed to two forms: most of the specimens belong to the species Thalassictis montadai, whereas one I3 is attributed to a large bone-cracking hyena. The material comes from the layers HAM 5 (11.62 Ma) and HAM 6 (slightly younger than 11.44 Ma) of Hammerschmiede (base of Late Miocene). The species Thalassictis montadai is well-known from late Aragonian and early Vallesian localities of central and southern Europe and west Asia. The presented material enables us to make a short review of the state-of-the-art about the fossil record of this species and to discuss its intraspecific variability. A gradual replacement of Thalassictis montadai, Thalassictis robusta and Hyaenictitherium wongii in Europe is demonstrated, until the arrival of canids during the latest Miocene. Additionally, the upper incisor of the large hyaenid creates some interesting questions concerning the first appearance of the crocutoid hyenas in the fossil record and their dominance over the percrocutoids.